2014
DOI: 10.1021/nl502780u
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Freestanding Monolayer Heterostructure of Graphene and Hexagonal Boron Nitride on Ir(111) with a Zigzag Boundary

Abstract: In-plane heterostructure of hexagonal boron nitride and graphene (h-BN-G) has become a focus of graphene research owing to its tunable bandgap and intriguing properties. We report herein the synthesis of a quasi-freestanding h-BN-G monolayer heterostructure on a weakly coupled Ir(111) substrate, where graphene and h-BN possess distinctly different heights and surface corrugations. An atomically sharp zigzag type boundary has been found to dominate the patching interface between graphene and h-BN, as evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
127
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 48 publications
26
127
2
Order By: Relevance
“…The shape of the dI/dV curve has also changed substantially from an asymmetric Vshape to a flatter, more parabolic, shape. Interestingly, our observations are very similar to results obtained by Liu et al [19] for graphene sheets on a hexagonal boron nitride layer. In any case the reconstructed germanene zigzag edges do not exhibit a pronounced metallic edge state.…”
supporting
confidence: 92%
“…The shape of the dI/dV curve has also changed substantially from an asymmetric Vshape to a flatter, more parabolic, shape. Interestingly, our observations are very similar to results obtained by Liu et al [19] for graphene sheets on a hexagonal boron nitride layer. In any case the reconstructed germanene zigzag edges do not exhibit a pronounced metallic edge state.…”
supporting
confidence: 92%
“…In general, there are two major edge types for graphene and MoS 2 : Zigzag and armchair. Since previous theoretical and experimental studies have shown that zigzag (ZZ) edges possess a lower formation energy and are more stable than armchair edges for both graphene 37,38 and MoS 2 39,40 in the growth, here only the zigzag-oriented interfaces are considered, which are named as ZZ interface, as shown in …”
Section: In-plane Interfacial Binding Between Mos 2 and Graphenementioning
confidence: 99%
“…26 Similarly, the interface of graphene/h-BN monolayer heterostructures 35 can also induce the mid gaps on the semiconductor part near the interface. These localized mid-gap states, which result from typical of defects in semiconductors, are important because they can affect the optical and transport properties of the material.…”
Section: Electronic Propertiesmentioning
confidence: 99%